Práticas de formação continuada de uma professora de educação física : ocultações, contradições e possibilidades - Heringer, Dionésio Anito Teixeira (2008)
It is about a study case which the formation practices are analyzed at the moment the Physical Education teacher of one of the municipal schools of Vitória tries to put into effect the formation proposals foreseen in the policy suggested by the Municipal Council of Education. It dialogues with authors who have been contributing with studies related to that field, trying to map the continuing formation in its conceptual evolution and in the ways it has been manifested. Consequently, it identifies the focus change in this movement that, considering a conception essentially positivist, advances to an epistemology of phenomenological and/or inter rational. It debates the responsibility of different instances linked to the formation movement: central management, formatting instances, schools and teachers, in the accomplishment of formation practices. It also discourses on some important occultation present in that field, generated by cognitive consensus that creates illusory projects for the situations realized under the optic of such consensus. In the analysis, it identifies some tensions and possibilities daily lived by teachers when trying to put into effect the formation actions foreseen in the politics. It stands out the central management as the one that has assumed, in a more effective way, the organization and definition of space/time of continuing formation. It points some possibilities of approximation with the Federal University of Espírito Santo (UFES) and calls attention for the necessity of an autonomous movement, thought and articulated through the formation instances, assumed with autonomy and criticism. It describes the conceptual coherence of the formation policy, if confronted with the programmatic ideology presented by the Municipal Education Council, at the same time that identifies some distance between what this conceptual basis shows and the foreseen actions by the central administration. It analyzes the school and the way how its organization favors and/or makes difficult the formation practices built and developed in an individual way and/or collective in the interior of such teaching unit, showing the policy of human resources of the City Hall as a determinant factor in the limitation of articulation possibilities of the collective of that teaching unit. Finally, it gets closer to the Physical Education teacher who is the a collaborator of the research to reveal how the school space is organized, which is determinant in the limitation or constitution of the formation practices and presents the level of involvement and complicity of the ones involved as an important factor of the investigated context.